Description of the advertisement call of a species without vocal sac: Craugastor gollmeri (Amphibia: Craugastoridae) - D., Roberto Ibáñez; A., César A. Jaramillo; Solís, Frank A. (Zootaxa, 2012)
The Central American frogs of the genus Craugastor consist of 113 species (Hedges et al. 2008; Frost 2011). Craugastor gollmeri (Peters) occurs in lowland to highland forests of central Panama, the Caribbean versant of western Panama and eastern Costa Rica, even extending into the Pacific versant in northwestern Costa Rica, within an altitudinal distribution range of 10–1520 m (Savage 2002). At some localities, C. gollmeri has been found to be an usual to common forest species, being primarily a diurnal species that inhabits leaf-litter on the forest floor (Ibáñez et al. 1995; Savage 2002). The snout-vent length (SVL) of adult frogs is 30–36.5 mm in males and 45–54 mm in females (Savage 1987). The males of gollmeri species group lack vocal slits and vocal sac (Savage 1987), and seem incapable of producing vocalizations (Savage 2002). Nonetheless, here we describe the vocalizations given by a male of C. gollmeri in captivity, considered to be advertisement calls (sensu Wells 1977). The role of advertisement calls in species recognition and reproductive isolation has been well established (Wells 2007), hence, the relevance of call characters in anuran phylogenetic and systematic studies (e.g., Hoskin 2004).